Outcome in design-specific comparisons between highly crosslinked and conventional polyethylene in total hip arthroplasty 163,368 hip replacements in the Nordic Arthroplasty Register Association database with 5-11 years of follow-up - Johanson PE; Furnes O; Havelin LI; Fenstad AM; Pedersen AB; Overgaard S; Garellick G; Makela K; Karrholm J (TAYLOR & FRANCIS LTD, 2022)
Background and purpose - Most registry studies regarding highly crosslinked polyethylene (XLPE) have focused on the overall revision risk. We compared the risk of cup and/or liner revision for specific cup and liner designs made of either XLPE or conventional polyethylene (CPE), regarding revision for any reason and revision due to aseptic loosening and/or osteolysis.Patients and methods - Using the Nordic Arthroplasty Register Association (NARA) database, we identified cup and liner designs where either XLPE or CPE had been used in more than 500 THAs performed for primary hip osteoarthritis. We assessed risk of revision for any reason and for aseptic loosening using Cox regression adjusted for age, sex, femoral head material and size, surgical approach, stem fixation, and presence of hydroxyapatite coating (uncemented cups).Results - The CPE version of the ZCA cup had a risk of revision for any reason similar to that of the XLPE version (p = 0.09), but showed a 6-fold higher risk of revision for aseptic loosening (p < 0.001). The CPE version of the Reflection All Poly cup had an 8-fold elevated risk of revision for any reason (p < 0.001) and a 5-fold increased risk of revision for aseptic loosening (p < 0.001). The Charnley Elite Ogee/Marathon cup and the Trilogy cup did not show such differences.Interpretation Whether XLPE has any advantage over CPE regarding revision risk may depend on the properties of the polyethylene materials being compared, as well as the respective cup designs, fixation type, and follow-up times. Further research is needed to elucidate how cup design factors interact with polyethylene type to affect the risk of revision.